Predictors of futile recanalization in patients with acute ischemic stroke undergoing mechanical thrombectomy in late time windows - Ni, Heng; Liu, Xinglong; Hang, Yu; Jia, Zhenyu; Cao, Yuezhou; Shi, Haibin; Liu, Sheng; Zhao, Linbo (Frontiers in Neurology, 2022)
Background and Purpose: Futile recanalization (FR), defined as functional dependence despite successful reperfusion, is common in patients who experience an acute stroke after thrombectomy. We aimed to determine the predictors of FR in patients who underwent thrombectomy in late time windows (6 hours or more after symptom onset). Methods: This retrospective review included patients who underwent thrombectomy for acute anterior circulation large vessel occlusion from October 2019 to June 2021. Successful reperfusion was defined as a modified Thrombolysis in Cerebral Infarction (mTICI) score of 2b/3. Functional dependence at 90 days was defined as a modified Rankin scale score of 3-6. Multivariate analysis and a receiver operating characteristic (ROC) curve were used to identify the predictors of FR in patients treated in delayed time windows. Results: Of the 99 patients included, FR was observed in 51 (51.5%). In the multivariate analysis, older age (OR, 1.12; 95% CI, 1.04-1.22; P = .005), female sex (OR, 3.79; 95% CI, 1.08-13.40; P = .038), a higher National Institutes of Health Stroke Score (NIHSS) score upon admission (OR, 1.11; 95% CI, 1.02-1.22; P = .023), and an increased number of passes per procedure (OR, 2.07; 95% CI, 1.11-3.86; P = .023) were independently associated with FR after thrombectomy. The ROC curve indicated that the model that combined age, female sex, baseline NIHSS score, and the number of passes per procedure (area under the curve, 0.84; 95% CI, 0.75-0.90, P < .001) was able to predict FR accurately. Conclusions: Older age, female sex, higher NIHSS score upon admission, and an increased number of passes per procedure were independent predictors of FR in patients who experienced acute ischemic strokes after thrombectomy in late time windows.